Effects of non-uniform distributions of gain and loss in photonic crystals. (15th December 2016) - Cerjan, Alexander; Fan, Shanhui
Abstract: We present a k · p theory of photonic crystals containing gain and loss in which the gain and loss are added to separate primitive cells of the underlying Hermitian system, thereby creating a supercell photonic crystal. We show that the supercell bands of this system can merge outward from the degenerate contour formed from folding the bands of the underlying Hermitian system into the supercell Brillouin zone, but that other accidental degeneracies in the band structure of the underlying Hermitian system do not yield band merging behavior. Finally, we show that the modal coupling matrix in PhCs with balanced gain and loss is trace-less, and thus the imaginary components of the eigenvalues can only move relative to one another as the strength of the gain and loss is varied, without any collective motion.